Medborgeridealer i forandring: Unge elevers fremtidsdrømme i det vestlige Nepal - Lind, Mette (Tidsskriftet Antropologi, 2010)
Birgitte Lind: Citizen Ideals in Transition. Young Students’ Dreams for the Future in Western Nepal This article explores and discusses citizen ideals as they get expressed through the future aspirations of young secondary school students in rural Nepal. It is based on ethnographic material collected in two secondary schools and among 9 and 10 class students in a hill district of far western Nepal in 2007 and 2008/9. The study is transpires in a period of political transition where new citizens have to be formed to face the new challenges. The young people have grown up during violent conflict and attended a school strongly shaped by the legacy of the past monarchy. Despite the abrupt changes caused by the end of a decade of violent conflict and of 238 years of Monarchy, there are continuities and historical legacies in the functioning and ideals of the schools. I argue that citizen ideals expressed through students’ future aspirations are created in a dialectical relationship between strong historical legacies, new equality ideals, the conflict and the existing transition. Using the notion of aspirations as an analytical lens reveals the interplay between “pastness, presentness and futureness”. Past experiences of conflict and schooling; present experiences as young in the school; and the future hope are all vital factors for understanding the ideals expressed in the students’ aspirations. Analysing the formation of citizen ideals through aspirations also indicates how young people interpret, reform and appropriate the ideals produced by the school. Coming from a highly structured social setting the young people’s future aspirations nonetheless reveal new ideals. These indicate a potential for future social change. Keywords: Citizenship, citizen ideals, aspirations, youth, schooling, political transition, Nepal.